Development of high-performance hypodermic needle penetration resistance flexible cotton fabric using patterned thermoplastic adhesive film. (December 2022) - Wu, R.; Mudzi, P.; Firouzi, D.; Ching, C.Y.; Selvaganapathy, P.R.
Abstract: Injuries caused by needle stick puncture are common and a concern in many industries, such as health services and waste collection. Personal protection against needle stick punctures currently use high-cost materials like high-density polyethylene (HDPE) woven fabric and Kevlar which compromises flexibility. In this paper, a low-cost, easy to produce, needle puncture resistant material is developed. Here, cotton fabric is overlaid by patterned Ethylene-Vinyl Acetate (EVA) based adhesive film and multiple layers are used that increase the needle penetration resistance by up to 478% as compared to a single layer of laminated fabric, while the flexibility decreased by only 12–49 %. Patterns of different shapes (hexagons and hexagons mixed with triangles) and sizes with nominal diameters ranging from 2.6 to 13.5 mm were tested, with the smaller nominal dimensional shapes having a greater flexibility. Patterned hot film had a similar needle penetration resistance as plain hot film but was significantly more flexible. Increasing the number of laminated fabric layers from 1 to 3 resulted in an increase in needle penetration resistance force from 2 N up to 8 N. Graphical Abstract: ga1